Kurikulum IMAD (`Idaad Almu'allimin Wa Ad-Duah) di Pesanan Islam Terpadu Daarul Fikri - Murtaqiatusholihat Murtaqiatusholihat; Mohammad Ali; Laksmi Dewi; Andria Pragholapati (Journal of Elementary School (JOES), 2022)
This study aims to explore the IMAD Curriculum (`Idaad Almu'allimin wa Ad-duah) at the Daarul Fikri Integrated Islamic Boarding School. This research is a library approach. The Daarul Fikri Integrated Islamic Boarding School, the Qobasat An-nur Foundation, implements a curriculum with the Superior Program for memorizing the Koran with mutqin, Linguistics, IMAD MD 4 (Muallim wa Ad-Duah) Dirosah Islamiyah (DI) curriculum or Islamic Science and equipped with a curriculum service (MIPA, Information Technology) and Living Skills. The typical curriculum of IMAD MD 4 (Muallim wa Ad-Duah) Dirosah Islamiyah (DI) or Islamic Sciences and equipped with an official curriculum (MIPA, Information Technology) and Living Skills. The concept of holistic Islamic education is able to touch the main objects: Ruhiyah, Aqliyah and Jasadiyah. Which aims to bring students who are able to achieve success in this world and the hereafter.